Development of a water quality index for the Laguna de Bay (Central Bay Area) - Araza, Dionisio M. (1991)
The "modified DELPHI" method was used in the development of a Water Quality Index (WQI) for the Laguna Lake. The followng steps are involved under this methodology: selection of parameters, determination of parameter weightings, establishment of parameter rating curves, establishment of a WQI classification based on WQI, and mathematical formulation and calculation of the WQI.Six (6) significant parameters are used in the WQI. These parameters and their respective weightings are: dissolved oxygen (0.23), pH (0.19), turbidity (0.15), nitrate (0.15), total dissolved solids (0.14), and total coliform (0.14). The rating curves of the 6 parameters were established using the average rating of the water experts. These curves were modified and refined by formulating equations that best described the analytical curves. The water quality of ant measured concentration of the respective parameters is determined either by extrapolating on the individual rating curves or using the derived equations. A water quality rating from 0 to 100 was used., where a good water quality is indicated by higher rating. A Water Quality Classification based on the numerical values and ranges of WQI is translated into qualitative description with the use of this Classification. The WQI formulation recommended for use is the Arithmetic Weighted Mean (AW) WQI=nE|s|Wi-Qi. The operational applications of the WQI were made using actual water quality data from the LLDA. the WQI was applied to the 4 major bay observation stations of the Lake: the Central Bay, the West Bay, the East Bay, and the South Bay. The annual average water quality data for 1986 and 1987 as well as the monthly average water quality data for 1987 of the 4 bays were used. The WQI obtained are from 72.0 (min.) to 73.0 (max.) for the annual average, and 62.1 (min.) to 83.9 (max) for the monthly average water quality data of the 4 bays. The results of both applications showed that the 4 bays had a "very good" to "excellent: water quality during these observed periods. The formulation can be used for current and future analysis to derive single and comprehensive description of the Lake's water quality.